Health and development : intersectoral linkages in India - Narayana, K. V. (Jaipur : Rawat Publications, 1997)
Relationship between status of health and socio economic development; a study.
Includes bibliographical references (p. 173-191) and index.
Keywords: Medical policy -- India; Health planning -- India; Social medicine -- India; Medical economics -- India